PENERAPAN PRINSIP KEHATI-HATIAN YANG DIGUNAKAN OLEH BANK PERKREDITAN RAKYAT DALAM MELANGSUNGKAN USAHA KREDIT - Sianipar, Samuel (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Credit is a financing option used by people or businesses to assist the growth of their businesses when the money they own is insufficient. Credit is a loan of money that must be paid back in installments or within a particular monetary limit set by a bank or other entity. A bank is a financial entity that receives cash from the public in the form of deposits and distributes them in the form of credit and/or other forms to help people better their living conditions. Commercial banks do business normally and/or according to Sharia standards, whilst rural banks conduct comparable business but do not provide payment traffic services. In addition to providing finance to microenterprises, BPR gets deposits from the community as well as small and medium enterprises. BPR is forbidden from engaging in operations involving foreign exchange, has just one in one province, and lacks the power to oversee payment traffic networks. To avoid inaccurate conclusions, BPR must be based on Article 8 of Law No. 10 of 1998.